Multi-Residue Analysis of Thyreostats in Animal Muscle Tissues by Hydrophilic Interaction Liquid Chromatography Tandem Mass Spectrometry: A Thorough Chromatographic Study - Anastasia S. Kritikou; Marilena E. Dasenaki; Niki C. Maragou; Marios G. Kostakis; Nikolaos S. Thomaidis (Separations)
Τhyreostats (TSs) are veterinary drugs used in livestock farming for fattening. Their administration is banned in the European Union since 1981, and their monitoring for food quality and safety control requires sensitive and confirmatory methods. The present study describes the development and validation of a hydrophilic interaction liquid chromatography tandem mass spectrometry (HILIC-MS/MS) method for the simultaneous determination of 2-thiouracil (TU), 6-methyl-2-thiouracil (MTU), 6-propyl-2-thiouracil (PTU), 6-phenyl-2-thiouracil (PhTU), tapazole (TAP), and 2-mercaptobenzimidazole (MBI) in bovine muscle tissues. Investigation of the retention mechanism of the six analytes on the selected amide-based stationary phase showed that hydrophilic partition was the dominant interaction. The sample preparation included extraction with ACN/H2O (80/20), followed by dispersive solid-phase extraction (d-SPE) with C18 sorbent and hexane partitioning. The method was validated according to European guidelines using internal standards, including isotopically labelled ones. The method’s LODs ranged between 2.8 ng g−1 (6-phenyl-2-thiouracil) and 4.1 ng g−1 (2-thiouracil). Application of the proposed method to 48 bovine tissue samples showed non-detectable results.